Theme Song Partai sebagai Komunikasi Politik: Analisis pada Lagu "PAN PAN PAN" - Muzzammil, Faisal (SOURCE : Jurnal Ilmu Komunikasi, 2023)
Partai Amanat Nasional (PAN) released a video for a song entitled "PAN..PAN..PAN" via the PAN TV YouTube account. The PAN song is a promotion and outreach within the framework of the 2024 General Election. The song, which was first released on YouTube PAN TV, has become a viral and trending topic on social media, even getting various comments from netizens and the public. Against the background of the phenomena and problems regarding the PAN song, the study aims to analyze the PAN song using a political communication approach and study. This study specifically aims to reveal more deeply about the following two entities, namely: (1) Forms of Political Communication in PAN Songs; (2) Political Communication Messages in PAN Songs. The analysis of this PAN song is based on the theory of the Bandwagon Effect and The Communicative Function Model. This study was conducted using a qualitative descriptive analysis method. Based on the results of analysis and data mining, two main findings were obtained in this study, namely: (1) The form of political communication in PAN songs includes political communication techniques in the form of the bandwagon effect which has three main effects on audiences, namely conformity, interpersonal influence and seeking status; (2) Political communication messages in the PAN song technically use the communicative function campaign model which consists of four stages, namely surfacing, primary, nomination and election.